Feasibility of creating an island divertor in the Uragan-2M torsatron - Lesnyakov, G.G.; Shapoval, A.N.; Pavlichenko, O.S. (Вопросы атомной науки и техники, 2012)
The concept of an island divertor appears the only suitable idea that may be helpful to make up for the absence of a natural helical divertor in the magnetic configuration. In this context, the paper presents and discusses the measured and calculated magnetic surface structures of different configuration modes, where large magnetic islands or their remains at the edge of the plasma volume may be used for experimental implementation of the island divertor. Единственной подходящей концепцией, с помощью которой можно восполнить отсутствие естественного винтового дивертора в магнитной конфигурации, является концепция островного дивертора. В этой связи представлены и обсуждаются измеренные и вычисленные структуры магнитных поверхностей разных режимов конфигурации, в которых большие магнитные острова или их остатки на краю плазменного объема можно использовать для экспериментальной реализации островного дивертора. Єдиною придатною концепцією, за допомогою якої можна заповнити відсутність природного гвинтового дивертора в магнітній конфігурації, є концепція острівного дивертора. У зв’язку с цим наведенo та обговорюються виміряні й обчислені структури магнітних поверхонь різних режимів конфігурації, у яких великі за розміром магнітні острови або їх залишки біля краю плазмового об’єму можна використати для експериментальної реалізації острівного дивертора.